WHEN ACCESS IS NOT ENOUGH: DIGITAL PEDAGOGY AND ACCESSIBILITY IN INDONESIAN EFL LEARNING ENVIRONMENTS - Budianto Hamuddin; Aprilia Yunda Supasa; Meutya Rizki Ramadhani; M. Fadhly Farhy Abbas (University of Kuningan, 2026)
Digital technologies have transformed English language education, yet technological access alone does not ensure meaningful participation in digital learning environments. This quantitative descriptive study investigated accessibility challenges experienced by Indonesian EFL students in digital English language learning platforms. The study addressed three research questions concerning the overall level of accessibility challenges, the contribution of technological, individual, pedagogical, and interactional dimensions, and the most influential dimension affecting students’ learning experiences. Data were collected from 78 undergraduate students in an English Language Education program at Universitas Lancang Kuning using a 20-item Likert-scale questionnaire distributed through purposive sampling. The instrument demonstrated acceptable reliability with Cronbach’s Alpha exceeding 0.70. Data were analyzed using descriptive statistical procedures with SPSS version 26. The findings revealed a moderate overall level of accessibility challenges (M = 3.00). Among the examined dimensions, pedagogical factors emerged as the most prominent challenge (M = 3.13), followed by engagement and interaction (M = 3.02), technological factors (M = 2.92), and individual factors (M = 2.82). The findings indicate that instructional design and interactional quality influence students’ digital learning experiences more strongly than technological infrastructure alone. The study reconceptualizes accessibility as a pedagogical and experiential construct, emphasizing the importance of interaction-rich digital pedagogy and responsive instructional practices in EFL contexts. Limitations include the use of self-reported data and single-site sampling.